Differential expression of Homeobox C11 protein in water buffalo Bubalus bubalis and its putative 3D structure - Sharma, Monal (BioMed Central, 2014)
BACKGROUND: The Homeobox (Hox) family complex contains 39 genes, clustered into four groups (A-D) all expressing in sequential manner. The HOX proteins are transcriptional factors involved in regulation of pattern formation of the anterio-posterior body axis across the species. Most of the Hox family genes have been studied with respect to their organization and expression during the embryonic stages. However, expression pattern of Homeobox C11 (Hoxc11) gene in the 5′ region, particularly in higher mammals remains largely unexplored. RESULTS: We cloned and expressed Homeobox C11 (Hoxc11) gene from water buffalo Bubalus bubalis. The recombinant HOXC11 protein expressed as inclusion bodies was solubilized in Tris buffer (10 mM, pH-6.5) and purified using Ni-NTA affinity column. The purity and molecular weight of HOXC11 protein (~33 kDa) were confirmed by SDS-PAGE and western blot analysis. Employing immunohistochemistry approach, we localized HOXC11 protein in the nuclei across the tissues of buffalo. Western blot analysis showed highest expression of HOXC11 protein in kidney and lung although its possible renal and respiratory roles are not yet established. Electrophoretic mobility shift assay (EMSA) demonstrated the specific binding of HOXC11 protein with the promoter element, CE-LPH1 of lactase-phlorizin hydrolase (LPH) gene showing reduced mobility of the protein-DNA complex, corroborating with earlier report on the possible role of this protein in intestinal functions. In silico analysis of HOXC11 showed predominance of α helices and presence of six conserved domains. We deduced the putative 3D structure of HOXC11 protein and fifteen possible DNA interacting residues within the homeodomain. CONCLUSIONS: Present study augments our understanding on the specific expression of HOXC11 protein in kidney and lung in water buffalo. The fifteen DNA interacting residues reported herein provide an opportunity to establish much broader structural and functional perspectives of HOXC11 protein in the context of genome analysis in general and animal biotechnology in particular. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2164-15-638) contains supplementary material, which is available to authorized users.